9c+4=

Simple and best practice solution for 9c+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9c+4= equation:


Simplifying
9c + 4 = 0

Reorder the terms:
4 + 9c = 0

Solving
4 + 9c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 9c = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 9c = 0 + -4
9c = 0 + -4

Combine like terms: 0 + -4 = -4
9c = -4

Divide each side by '9'.
c = -0.4444444444

Simplifying
c = -0.4444444444

See similar equations:

| (x+2)(2x^2+9x+8)=0 | | -2.125+-6.875= | | (3x-3)(3x-4)=0 | | (x+3)(x^2-6x+5)=0 | | 10k-(k+3)+2= | | 3.1+(-7.6)= | | 6(n-8)-4n= | | (-0.1)-4.8= | | F(x)=(8x+10x+6)(x+0.5) | | -(1.2)-(-6.8)= | | 6(3x+1)=2x-6x | | (x-6)(x^2+2x-4)=0 | | 5y=15x+20 | | 14x+4y=-76 | | 4.9x+44=19.1 | | 7sinx+5=2cos^2x | | 7x-2(-3x+4)=18 | | 12+(-10)+(-2)= | | 5+45=-5(8x-10) | | (7x+4)=(13x+6) | | 4/60= | | 2(2+j)=4(j+10) | | -7+5-(-10)= | | 5((-1)+3)= | | (3x^2-6x-3)(7x+8)=0 | | 3.1=(10*2.5)+(13*3)+(4*x)/10+12+x | | 9x-6+7x=8x+6 | | 7-(2z-3)=7-3z | | -19-(-21)= | | f(x)=2+4x | | 80+9h=224 | | 4x^6=81 |

Equations solver categories